Tree species of South America central savanna: endemism, marginal areas and the relationship with other biomes - Renata D. Françoso; Ricardo F. Haidar; Ricardo B. Machado (Acta Botânica Brasílica, 2016)
Biological knowledge is important for guidance of conservation polices. In the Cerrado, an extremely diverse biome, the last synthesis of floristic knowledge has more than ten years. To understand the progress on the information, our aim was quantify the tree species of the Cerrado, and assess their distribution. We compiled 167 inventories and rapid surveys of tree species, corresponding to 625 sites. We accessed the species distributions in the Brazilian biomes, and estimated the number of species in the savannas of Cerrado using four algorithms. We observed a greater local richness in more central regions of the biome, but due to high beta diversity, more peripheral regions presented a greater cumulative richness. The Atlantic Forest was the most important neighbouring biome, influencing the floristic composition of the Cerrado. The proportion of typical Cerrado species was 16%. The highest proportion of endemic species is possibly found in other life forms, and it is crucial that these species are included in inventories and floristic surveys. To guide new studies and help supplement the knowledge of the Cerrado's flora, we identified the main sampling gaps, located mainly in ecotonal regions, which are responsible for the largest number of species recorded in studies of the Cerrado.